Gallium‐Based Liquid Metal Reaction Media for Interfacial Precipitation of Bismuth Nanomaterials with Controlled Phases and Morphologies. (7th November 2021) - Mayyas, Mohannad; Khoshmanesh, Khashayar; Kumar, Priyank; Mousavi, Maedehsadat; Tang, Jianbo; Ghasemian, Mohammad B.; Yang, Jiong; Wang, Yifang; Baharfar, Mahroo; Rahim, Md. Arifur; Xie, Wanjie; Allioux, Francois‐Marie; et al.
Abstract: Liquid–liquid interfaces of liquid alloys with electrolytic solutions present fertile platforms for realizing exciting interfacial phenomena that can be devised to process alloys and produce nanomaterials. Here, such an interface is established by immersing a gallium–bismuth binary liquid alloy into aqueous electrolytes. It is shown that the application of a negative voltage to this interface results in a rapid and complete liberation of bismuth nanostructures from liquid gallium. The set of conditions that govern the chemistry of the interface can be adjusted to control the oxidation state, morphology, and crystal structure of the expelled bismuth. By changing the conditions; nanotubular, atomically thin plates, and sea‐urchin‐shaped bismuth oxide morphologies are obtained. The process can also control the crystal phase of bismuth oxide as monoclinic (α), tetragonal (β), or body‐centered cubic (γ). The addition of ascorbic acid to the electrolyte is observed to prevent the oxidation of the expelled entities, resulting in bismuth metal nanoparticles. Ab initio molecular dynamics and computational fluid dynamics simulations are performed to elucidate this rapid phase separation at the interface. This knowledge will potentially lead to new pathways for using alloys as reaction media to refine metals while simultaneously producing nanomaterials for various applications. Abstract : Gallium‐based liquid alloys establish liquid–liquid interfaces with electrolytic solutions. Applying a cathodic voltage to the liquid–liquid interface of eutectic gallium–bismuth binary liquid alloy triggers a phase separation where bismuth solute atoms precipitate rapidly from the interface. Bismuth atoms precipitate from the liquid alloy as nanosized entities that can be controlled to produce bismuth and bismuth oxide nanomaterials.